THE EFFECT OF UMBILICAL CORD CARE ON THE DURATION OF CORD SEPARATION IN NEWBORNS - Brigita Diah Pitaloka; Atun Wigati; Diah Andriani (Jurnal Kebidanan Khatulistiwa, 2026)
Background: Umbilical cord care is an essential component of newborn care as it influences cord separation time and the risk of neonatal infection. Open and closed cord care methods are commonly used in the community, yet their effectiveness remains debated. Purpose: This study aimed to analyze the effect of open compared to closed umbilical cord care methods on cord separation time among newborns. Methods: This quantitative study employed a quasi-experimental posttest only control group design involving 60 newborns divided equally into open and closed care groups. Data were collected through observation until natural cord separation occurred. Descriptive analysis was conducted, followed by Shapiro–Wilk normality testing and Mann–Whitney test due to non-normal data distribution. Results: The results showed that the mean separation time in the open care group was 5.40 days, while in the closed care group it was 8.47 days. The Mann–Whitney test revealed U=6.000; Z=−6.654; p=0.000 (p